2022
DOI: 10.3390/su142215126
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Thermal Environment during Summer in Coastal Open Space and Research on Evaluating the Cooling Effect: A Case Study of May Fourth Square, Qingdao

Abstract: Urban green space is considered an important part of urban ecological construction be-cause of the efficiency of green space in reducing ambient temperature. It was previously reported that the quantity and layout of arbors and paving are very important factors for cooling. To research the combination mode of the quantity and layout of arbors and paving able to effectively lower the temperature during the summer in a coastal open space environment where little architecture exists, we built a numerical model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These studies lack any CFD model assessment for scenario comparison or subjective thermal perception evaluation. Most studies are with microclimate data monitoring, CFD model scenario simulation with thermal comfort assessment for different mitigation strategies, and an evaluation of microclimatic improvements [15,18,81,82,84,[88][89][90][91]94,95,137,[153][154][155][156][157][158][159][160][161][162][163][164][165][166]. Developing and testing alternatives, such as the process "research by design", this research paper describes design outcome, evaluation, and design process-mitigation model or strategy.…”
Section: Iiie Cluster Design Scenario Evaluationmentioning
confidence: 99%
“…These studies lack any CFD model assessment for scenario comparison or subjective thermal perception evaluation. Most studies are with microclimate data monitoring, CFD model scenario simulation with thermal comfort assessment for different mitigation strategies, and an evaluation of microclimatic improvements [15,18,81,82,84,[88][89][90][91]94,95,137,[153][154][155][156][157][158][159][160][161][162][163][164][165][166]. Developing and testing alternatives, such as the process "research by design", this research paper describes design outcome, evaluation, and design process-mitigation model or strategy.…”
Section: Iiie Cluster Design Scenario Evaluationmentioning
confidence: 99%
“…These air ducts can be enhanced by planting dense vegetation and controlling the height and density of buildings on both sides of the corridor [25]. It was found that setting the passageway conformed to the sea breeze by arbors and close planting at the air outlet effectively reduced the site temperature [26].…”
Section: Of 22mentioning
confidence: 99%